Antifungal Susceptibility Data and Epidemiological Distribution of Candida spp.: An In Vitro Five-Year Evaluation at University Hospital Policlinico of Catania and a Comprehensive Literature Review - Maddalena Calvo; Guido Scalia; Laura Trovato (MDPI AG, 2024)
Background: Invasive fungal infections represent a concerning healthcare issue, with Candida spp. reported as the main aetiological agent. Candida spp. bloodstream infections show high mortality rates, indicating increasing antifungal-resistance episodes as a contributing feature. Despite the global prevalence of C. albicans, non-albicans species emerged as significant in the last decades. Methods: The present manuscript reports a five-year evaluation on Candida spp. bloodstream isolates and their antifungal susceptibility profiles, aiming to enrich the literature and epidemiological data. Results: According to the gathered data, antifungal-resistance cases remained uncommon. However, the study revealed rare resistance phenotypes such as a single case of pan-echinocandin resistance C. albicans. Conclusions: Finally, a comprehensive review of Candida spp. antifungal resistance integrates the data, emphasizing the extreme species-specific variability and the consequent importance of always providing species identification.